PARS (PREVIEW, ASK, READ, AND SUMMARIZE (PARS) STRATEGY IN READING COMPREHENSION - Ibrahim, Nelvia (JEE (Journal of English Education), 2023)
This article suggests how many strategies are used in the teaching and learning process, teachers need to be more creative and innovative in creating new things. This strategy is not yet well known by students and is a new challenge for teachers to display. If you listen to the steps, it is almost the same as SQ3R. Still, the difference is that the PARS strategy is that students preview the text before reading, they look at headings; words that are bolded or underlined; and pictures, tables, graphs, and other key information and the main point is students preview the entire of passage or text before they read, suddenly the students generate some question based on what they have already previewed. Therefore, the students read to find out the answers to their questions. After reading, the students write a summary of the text that they have read. It is hoped that students can see big ideas and details that need support in the form of relational structures and are expected to foster students' interest in reading for the better and supported by the right strategy, and one of them is the use PARS Strategy.